2020
DOI: 10.1177/0011000020949146
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Evidence of the Short Almost Perfect Scale (SAPS) in Brazil

Abstract: Perfectionism can be understood as a personality trait that establishes excessively high standards for the performance of individuals and ostensibly critical self-evaluations. It is associated with a range of variables, such as anxiety, suicidal tendencies, depression, and low satisfaction with life. The Short Almost Perfect Scale (SAPS) overcame some limitations of previous measures (e.g., ambiguity, nonnecessary factors). In the present research, we provide psychometric evidence of the adequacy of the SAPS i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
(161 reference statements)
0
0
0
Order By: Relevance
“…Examination of the SAPS indicated that a two-factor model held for medical students, and this scale was utilized for all subsequent examinations. This finding in favor of SAPS is consistent with findings in other populations (Rice et al, 2014;Kira et al, 2018;de Holanda et al, 2021), and suggests that the SAPS is likely preferred in the medical student population.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Examination of the SAPS indicated that a two-factor model held for medical students, and this scale was utilized for all subsequent examinations. This finding in favor of SAPS is consistent with findings in other populations (Rice et al, 2014;Kira et al, 2018;de Holanda et al, 2021), and suggests that the SAPS is likely preferred in the medical student population.…”
Section: Discussionsupporting
confidence: 88%
“…Most validity studies of the APS have been completed in convenience samples of university students in psychology classes, which resulted in female-predominant samples. MI results have been mixed by gender, with most studies supporting invariance (Rice et al, 2014;Kira et al, 2018;de Holanda et al, 2021), while a few have indicated at least partial non-invariance at the scalar (intercept) level (Rice et al, 2019). In our population, indeterminate measurement invariance results suggest that any measured mean differences in perfectionism by gender may result from the ways groups perceive perfectionism or reacted to the scale questions, rather than actual differences in the mean levels of perfectionism, and that future work is needed to confirm MI by gender in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If they have high Standards but Discrepancy is less than 3.5, they might be what we called "adaptive" perfectionists. (K. Rice, personal communication, October 25, 2022) The "Psychometric evidence of the Short Almost Perfect Scale (SAPS) in Brazil" psychometric study by Coelho and colleagues of the SAPS used a Brazilian online sample (aged 14-67) and found that the scale is an adequate assessment of perfectionism, for both validity and reliability (Coelho et al, 2021). The SAPS presents a two-factor structure that was replicated in this study for standards and discrepancy perfectionism.…”
Section: Short Almost Perfect Scale (Saps)mentioning
confidence: 52%